"Like Human Beings": Responsive Relationships and Institutional Flexibility at a Rural Community College - Caitlin Howley; Barbara Chavis; John Kester (Journal of Research in Rural Education, 2013)
Drawing on data from a program serving displaced workers and adult students, this article explores how students at a small rural-serving community college in North Carolina believe rurality infl uences their retention. We review the research and descriptive literature on rural community college challenges, advantages, and approaches to supporting non-traditional students. We then describe our research design, including characteristics of the study site and the program for displaced workers and adult students. Analyzing student interviews and staff refl ections, we fi nd that only half of interviewed students view the community in which their college is located as rural. For those who do consider the area rural, the loss of economic opportunity defi nes rurality, rather than constitutive attributes such as access to the natural environment or tightly-knit local relationships. Regardless of their perception of the community as rural or non-rural, all of our interviewees reported that responsive faculty and staff and institutional fl exibility contributed to their postsecondary persistence. Rural constraints such as family commitments and lack of entertainment options may also ironically support retention for some students. We conclude with a discussion of implications of our study for policy, practice and research.